2019
DOI: 10.2174/0929866526666190822165812
|View full text |Cite
|
Sign up to set email alerts
|

Mini Review on Antimicrobial Peptides, Sources, Mechanism and Recent Applications

Abstract: Antimicrobial peptides in recent years have gained increased interest among scientists, health professionals and the pharmaceutical companies owing to their therapeutic potential. These are low molecular weight proteins with broad range antimicrobial and immuno modulatory activities against infectious bacteria (Gram positive and Gram negative), viruses and fungi. Inability of micro-organisms to develop resistance against most of the antimicrobial peptide has made them as an efficient product which can greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 155 publications
1
124
0
Order By: Relevance
“…Multiple of the studies which have evaluated the nature of MSC antimicrobial activity have revealed a role for antimicrobial peptides (AMPs) in the process. AMPs are a diverse class of low molecular weight proteins produced as a first line of defense against pathogens such as bacteria, fungi and viruses 72 . In revolutionary work by Krasnodembskaya et al it was shown that the antibacterial effect of MSCs was partly mediated by LL-37, an AMP.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…Multiple of the studies which have evaluated the nature of MSC antimicrobial activity have revealed a role for antimicrobial peptides (AMPs) in the process. AMPs are a diverse class of low molecular weight proteins produced as a first line of defense against pathogens such as bacteria, fungi and viruses 72 . In revolutionary work by Krasnodembskaya et al it was shown that the antibacterial effect of MSCs was partly mediated by LL-37, an AMP.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…It has been shown that AMPs are capable of altering DNA morphology, with possible effects of nucleic acid disruption and fragmentation [ 161 ]. For example, buforin II and takiplesin bind to DNA, pleurocidin and indolicidin inhibit the DNA, RNA and protein synthesis (biosynthetic processes), drosocin and pyrrhocoricin reduce enzymatic activity, mersacidin inhibits the biosynthesis of the cell wall [ 162 ]. The study of supramolecular structures formed between DNA and AMPs has demonstrated a correlation between these structures and their ability to activate toll-like receptor 9 (TLR9), an important receptor expressed in cells of the immune system [ 163 ].…”
Section: Mechanisms Of Antimicrobial Action Of Peptidesmentioning
confidence: 99%
“…Antimicrobial peptides (AMPs) have been increasingly investigated as promising therapeutic alternatives to conventional antimicrobial therapies. This family of molecules are constituted by low molecular weight proteins, discovered from both prokaryotes and eukaryotes, and are produced as part of innate immune response mechanisms against microorganisms [10]. AMPs typically exhibit broad-range antimicrobial action [11,12] and immunomodulatory properties [13,14].…”
Section: Introductionmentioning
confidence: 99%